Pengaruh Doktrin Konstruktivisme Budaya Bangsa Belanda Sebagai Negara Kolonialisme Terhadap Tipologi Bangsa Indonesia Sebagai Negara Post-Kolonialisme - Aftariansyah, Muhammad Diaz; Hanifa, Silma; Aepudin, Saepul (UIN Sunan Gunung Djati Bandung, 2025)
This research explores the significant impact and complex implications of Dutch colonial cultural constructivism on post-colonial Indonesia. Through a combined approach of historical analysis, literature review, and empirical case studies, the study unveils how the cultural constructivism of the colonial powers, such as the social classification of